“Viles personnes”: the plebeian multitudes in Charles Loyseau’s Traité des ordres - Patterson, J (Routledge, 2016)
Charles Loyseau’s Traité des ordres et simples dignitez (1610) is well known to historians for its apparent “anatomy” of France’s social hierarchy in the Ancien Régime. Whilst Loyseau was mostly preoccupied with the elites and their varying levels of dignity, his treatise nonetheless provides an important window on the multitudinous plebeian orders. Loyseau hesitantly stratifies four tiers of “viles personnes” (cultivators, artisans, casual workmen, and beggars). Each of these groups puts strain on his conceptual framework of dignity and order; only beggars emerge as fully vile. The plebeian multitudes of the Traité des ordres engage in menial, unstable, but in many cases still worthwhile occupations. By comparing Loyseau’s views with those of contemporaries (Louis Turquet de Mayerne and Antoine de Montchrestien) we may better understand his conception of “viles personnes” as the first stages of an emergent discourse on political economy: harnessing the economic potential of France’s poorest.